IMF Research Bulletin, December 2015. (IMF Research Bulletin; IMF Research Bulletin ;, 2016)
The December issue of the Research Bulletin looks at 'Seven Questions about Climate Change' (Rabah Arezki and Akito Matsumoto). The Research Summaries review 'Winning the Oil Lottery: The Impact of Natural Resource Extraction on Growth' (Tiago Cavalcanti, Daniel Da Mata, and Frederik Toscani) and 'Malaysia: Achieving High-Income Status through Resilience and Inclusive Growth' (Alex Mourmouras and Naimh Sheridan). The issue also includes regular updates on new IMF Working Papers, Staff Discussion Notes, IMF books, and the IMF Economic Review.